2022
DOI: 10.1186/s12864-022-08970-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study uncovers major genetic loci associated with flowering time in response to active accumulated temperature in wild soybean population

Abstract: Flowering time and active accumulated temperature (AAT) are two key factors that limit the expanded production especially for soybean across different regions. Wild soybean provides an important germplasm for functional genomics study in cultivar soybean. However, the studies on genetic basis underlying flowering time in response to AAT especially in wild soybean were rarely reported. In this study, we used 294 wild soybean accessions derived from major soybean production region characterized by different AAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The broad geographic distribution and resilience to harsh environmental conditions suggest a wealth of adaptive genes within G. soja [ 9 , 11 ]. Numerous beneficial genes or genetic loci have been identified in G. soja resources, including those conferring abiotic resistance [ 18 , 19 , 20 , 21 ], biotic resistance [ 22 ], and adaptation to various environmental conditions [ 9 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad geographic distribution and resilience to harsh environmental conditions suggest a wealth of adaptive genes within G. soja [ 9 , 11 ]. Numerous beneficial genes or genetic loci have been identified in G. soja resources, including those conferring abiotic resistance [ 18 , 19 , 20 , 21 ], biotic resistance [ 22 ], and adaptation to various environmental conditions [ 9 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that the introgression from adapted sympatric wild soybeans facilitated the local adaptation of landraces during the expansion of cultivated soybean [ 17 ]. Numerous beneficial genes or genetic loci have been identified from G. soja resources, including those conferring abiotic resistance [ 18 , 19 , 20 , 21 ], biotic resistance [ 22 ], and adaptation to various environmental conditions [ 23 , 24 , 25 , 26 ]. Consequently, wild soybean represents a valuable gene reservoir for the genetic enhancement of cultivated soybeans, providing them with the capacity to adapt to new environments.…”
Section: Introductionmentioning
confidence: 99%
“…But there are few studies that focus on the adaptation to temperature changes. Yang et al identified three genes in 294 wild soybean accessions distributed at chromosomes 2, 4, and 9 that are associated with the pathways of photosynthesis light reaction and actin filament binding [11]. Zhu et al located a homolog of the vernalization pathway gene GmFRL1 in soybean [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chen [12] found that elevated soil temperature would lead to an increase in soil effective accumulated temperature, and the effective accumulated temperature was linearly related to the germination progress of Fraxinus chinensis. Major genetic loci related to flowering under accumulated temperature response were identified in soybean populations [13]. There are few reports studying the flowering period of lotus through accumulated temperature, but systematic studies are still lacking [14].…”
Section: Introductionmentioning
confidence: 99%